1970
DOI: 10.1029/jb075i017p03367
|View full text |Cite
|
Sign up to set email alerts
|

Experimental isostasy: 2. An isostatic model for the U.S.A. derived from gravity and topographic data

Abstract: By using a fast Fourier transform algorithm, the two‐dimensional transform of the Bouguer anomaly (with terrain correction) BA (kx, ky), free‐air anomaly FA ( kx, Ky), and topography H (kx, ky) on a 32‐km grid has been obtained, being based on some 80,000 actual gravity observations and on the Bouguer anomaly map of the U.S.A. The azimuthally symmetric, real function R (k) = 〈Re (BA (kx, ky)/H(kx, ky))〉, averaged over azimuth so as to minimize the geological ‘noise,’ gives the transfer function of the earth to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(48 citation statements)
references
References 13 publications
(5 reference statements)
1
47
0
Order By: Relevance
“…The admittance is based completely on the observed relationship between gravity and bathymetry and is not tied to any isostatic model. However, Dorman and Lewis (1970), Lewis and Dorman (1970), McKenzie and Bowin (1976), Walcott (1976), Watts (1978), Banks et al (1977) and Louden (1981) showed that admittance could be easily compared with admittance calculated for various isostatic models based on different hypotheses of compensation.…”
Section: Methodsmentioning
confidence: 96%
“…The admittance is based completely on the observed relationship between gravity and bathymetry and is not tied to any isostatic model. However, Dorman and Lewis (1970), Lewis and Dorman (1970), McKenzie and Bowin (1976), Walcott (1976), Watts (1978), Banks et al (1977) and Louden (1981) showed that admittance could be easily compared with admittance calculated for various isostatic models based on different hypotheses of compensation.…”
Section: Methodsmentioning
confidence: 96%
“…In this method, the admittance (Lewis andDorman 1970, McKenzie andBowin 1976) is calculated using the line-of-sight accelerations of the Mars Global Surveyor (MGS) in its orbit, as a proxy for the gravity field, and the MOLA topography. The admittance spectrum for VM could be modeled by a best-fit elastic thickness of around 50 km, the short-wavelength admittance estimates being consistent with a crustal density of around 2.4 Mg m −3 .…”
Section: Valles Marineris (Vm) (Approximatelymentioning
confidence: 99%
“…The main assumption is that the wavelength of any subsurface a.nomalous distribution of mass must be much shorter or much longer than the dimensions of the bathymetric feature being studied. Lewis and Dorman (1970) pointed out that this method is successful only for topography with wavelengths much shorter than those of gravity anomalies produced by regional isostatic compensation. This technique is not valid for a seamount ifit has a local gravity "root" or a large magma chamber (Le Pichon and TaI wani, 1964).…”
Section: Three-dimensional Models Of Sio and Ita Mai Tai Guyotsmentioning
confidence: 99%